Formation of a Cluster-Managing Model for an Innovative Development in a Region of the Russian Federation; Mediterranean Journal of Social Sciences; Vol. 6, № 3 S5 - Strelyaeva A. E. Anna Evgenjevna (2015, 2015)
Title screen